Water, Hygiene, and Sanitation Risk Factors towards Stunting among Children (0-14 years): A Systematic Literature Review - Sulistiyorini, Desy; Ekaningrum, Annisa Yuri (Poltekkes Kemenkes Palu, 2025)
Background: Stunting remains a major public health problem in low- and middle-income countries and is closely linked to inadequate water, sanitation, and hygiene (WASH) conditions through repeated infections and impaired nutrient absorption. Evidence on the role of WASH across a broader child age range remains limited. This study aimed to systematically review the association between WASH factors and stunting among children aged 0–14 years. Methods: A systematic literature review was conducted following PRISMA guidelines. Articles published in English between 2013 and 2023 were retrieved from PubMed and Scopus using the keywords “water,” “sanitation,” “hygiene,” “WASH,” and “stunting.” Observational studies conducted in low- and middle-income countries were included. Two reviewers independently screened titles, abstracts, and full texts. Results: A total of 83 studies were included, predominantly cross-sectional in design. Most studies were conducted in East Africa and Southeast Asia. Consistent evidence showed that unimproved water sources, lack of water treatment, poor sanitation facilities, open defecation, unsafe disposal of child feces, and inadequate hygiene practices—particularly handwashing—were significantly associated with increased risk of stunting. Improved water access, sanitation infrastructure, and hygiene behaviors were identified as protective factors. Conclusion: Inadequate WASH conditions are strongly associated with childhood stunting. Integrating WASH interventions, especially sanitation and hygiene improvements, with nutrition programs is essential to reduce stunting and promote healthy child growth in low- and middle-income countries.